Calmodulin 2 Mutation N98S Is Associated with Unexplained Cardiac Arrest in Infants Due to Low Clinical Penetrance Electrical Disorders. - Juan Jiménez-Jáimez (PLoS ONE, 2016)
BACKGROUND:Calmodulin 1, 2 and 3 (CALM) mutations have been found to cause cardiac arrest in children at a very early age. The underlying aetiology described is long QT syndrome (LQTS), catecholaminergic polymorphic ventricular tachycardia (CPVT) and idiopathic ventricular fibrillation (IVF). Little phenotypical data about CALM2 mutations is available. OBJECTIVES:The aim of this paper is to describe the clinical manifestations of the Asn98Ser mutation in CALM2 in two unrelated children in southern Spain with apparently unexplained cardiac arrest/death. METHODS:Two unrelated children aged 4 and 7, who were born to healthy parents, were studied. Both presented with sudden cardiac arrest. The first was resuscitated after a VF episode, and the second died suddenly. In both cases the baseline QTc interval was within normal limits. Peripheral blood DNA was available to perform targeted gene sequencing. RESULTS:The surviving 4-year-old girl had a positive epinephrine test for LQTS, and polymorphic ventricular ectopic beats were seen on a previous 24-hour Holter recording from the deceased 7-year-old boy, suggestive of a possible underlying CPVT phenotype. A p.Asn98Ser mutation in CALM2 was detected in both cases. This affected a highly conserved across species residue, and the location in the protein was adjacent to critical calcium binding loops in the calmodulin carboxyl-terminal domain, predicting a high pathogenic effect. CONCLUSIONS:Human calmodulin 2 mutation p.Asn98Ser is associated with sudden cardiac death in childhood with a variable clinical penetrance. Our results provide new phenotypical information about clinical behaviour of this mutation.